Alter ego : twenty confronting views on the European experience - Snel, Guido, 1972- (Amsterdam University Press : Salomé, 2004)
Frank, illuminating and poignant immigrant tales from twenty of Europe's writers, artists, politicians and scholars looking back at their roots, their journeys and their divided loyalties.